(untitled) (Al-Academy, 2025)
The research discussed the topic of infinite complexity in accordance with its references to fractal geometry in fabric and fashion design. It did so by discussing the fundamental concepts starting from the research problem, which was represented by the question: What is the role of infinite complexity in fractal geometry in fabric and fashion design? It then moved on to the research objective, which was to define the nature of infinite complexity through the propositions of fractal geometry and to explain its formal and structural nature in fabric and fashion applications. This was achieved by addressing the concepts of fractal geometry and its characteristics, such as self-similarity, irregularity, fractal dimension, chaos, and defining the nature of infinite complexity and its formal features, which were identified as: infinite depth and details, visual appeal, non-traditional aesthetics, inspiration from nature, and storytelling. Three samples were then selected of the designers (Iris Van Herpen) in her collection (Voltage) for the year 2015, (Alexander McQueen) in his collection for the year 2009 titled (Plato’s Atlantis), and (Issey Miyake) in his collection for the year 2010 titled (Issey Miyake’s 132 5). Several conclusions were reached, the most important of which was the appearance of the models with formal and structural characteristics that achieved irregularity and complexity. They were distinguished by formal and structural characteristics, structural interplays, infinite depth, and multiple details that gave them different visual appeal and non-traditional aesthetics